An Empirical Study on Risk Taking in Tournaments - Christian Grund; Oliver Gürtler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
Individuals faced by a tournament can oftentimes not only choose their effort level, but also the risk level of their strategy. There are some theoretical contributions on risk taking in tournaments, which mainly point out disadvantages with respect to exerted effort. Empirical evidence is rare. In this paper we analyze risk taking behavior of professional soccer coaches. We find that risk taking concerning the kind of observed substitutions is, indeed, relevant. However, risk taking does not pay off.
Keywords: 330